Effect of prenatal hypoxia and its pharmacologic correction on the level of apoptosis-associated proteins in the brain of rat offspring - Aliyeva, O. G.; Алієва, Олена Геннадіївна (My University, 2024)
Apoptosis in the developing organism maintains tissue homeostasis by a balance of active cell proliferation and programmed cell death. In response to negative factors, including oxygen deficiency, in the cells pro-apoptotic caspases are activated, triggering the mechanisms of apoptosis. Hypoxia during the intrauterine period can lead to irreversible changes in the structure and function of the developing brain and nervous system.
Keywords: тези доповідей